Change in the hepatic profile of hepatitis C virus genotype 4–infected patients with compensated cirrhosis receiving ombitasvir, paritaprevir, and ritonavir plus ribavirin: A subanalysis of the AGATE‐II study. Issue 11 (16th July 2018) - Waked, Imam; Esmat, Gamal; Fouad, Rabab; Allam, Naglaa; Hassany, Mohamed; Mohey, Mohammad; Shiha, Gamal; Soliman, Reham; Qaqish, Roula B.; Hall, Coleen; Alami, Negar N.; Kopecky‐Bromberg, Sarah; et al.
Abstract : In AGATE‐II, treatment with ombitasvir coformulated with paritaprevir/ritonavir plus ribavirin (RBV) in Egyptians infected with hepatitis C virus genotype 4 resulted in high rates of sustained virologic response at post‐treatment week 12. This subanalysis examined the effects of treatment in AGATE‐II on liver biomarkers in patients with compensated cirrhosis. AGATE‐II was a phase 3, open‐label, partly randomized trial of ombitasvir/paritaprevir/ritonavir with weight‐based RBV daily once in treatment‐naive or treatment‐experienced patients. Patients without cirrhosis received treatment for 12 weeks and patients with compensated cirrhosis were randomized 1:1 to the same regimen for either 12 or 24 weeks. Sixty patients with compensated cirrhosis were randomized to treatment for 12 weeks (n = 31) or 24 weeks (n = 29). In the 12‐week arm, significant improvements were observed in biomarkers of liver injury (alanine aminotransferase: –53.7 U/L, P < 0.001; aspartate aminotransferase: –35.9 U/L, P < 0.001) and liver fibrosis (aspartate aminotransferase to platelet ratio index: –0.987, P < 0.001; fibrosis‐4 index: –1.165, P < 0.001). Similar results were reported in the 24‐week arm. Treatment with ombitasvir/paritaprevir/ritonavir plus RBV in hepatitis C virus genotype, 4‐infected Egyptians with compensated cirrhosis resulted in improvements in certain biomarkers of liver synthetic function, injury, and fibrosis, independent of treatment duration.